Living donor liver transplantation for Budd‒Chiari syndrome with right posterior segment graft and patch plasty using the superficial femoral vein: a case report - Norikazu Une; Kazuaki Tokodai; Norifumi Kanai; Yoshikatsu Saitoh; Mineto Ohta; Kengo Sasaki; Koji Miyazawa; Toshiaki Kashiwadate; Atsushi Fujio; Wataru Nakanishi; Shigehito Miyagi; Michiaki Unno; et al. (Surgical Case Reports)
Abstract Background In living donor liver transplantation (LDLT) for patients with Budd‒Chiari syndrome (BCS), there are several concerns about reconstruction of the inferior vena cava (IVC) and hepatic veins. Herein, we report the case of a patient with BCS who underwent LDLT with right posterior segment graft (RPSG) and patch plasty for reconstruction of the hepatic venous outflow, using the patient’s own superficial femoral vein (SFV). Case presentation A 19-year-old man, who was diagnosed with primary BCS, underwent LDLT. His main hepatic veins were totally obstructed, and membranous stenosis was seen in the IVC. The LDLT donor was his mother; however, liver volumetric analysis showed that only her RPSG was appropriate. In the recipient surgery, 16 cm of the left SFV was harvested and was cut longitudinally and opened. The right hepatic vein (RHV) of the RPSG was anastomosed to the sidewall of the SFV graft. After explantation of native diseased liver was completed, the stenotic and thickened wall of the IVC was widely resected, and a large anastomotic orifice was created. Patch cavoplasty was performed with the RHV‒SFV graft patch. After portal reperfusion started, hepatic venous outflow was satisfactory, and there was no venous graft congestion. Both his postoperative course and his long-term course after discharge were uneventful. Conclusions In LDLT for BCS patients, ingenuity is required for the reconstruction of venous outflow. The SFV patch can be safely harvested from liver transplant recipients and is suitable for venous reconstruction. In addition, RPSG is an alternative type of liver graft for LDLT if a conventional right- or left-lobe graft cannot be used.